2011
DOI: 10.1038/labinvest.2011.60
|View full text |Cite
|
Sign up to set email alerts
|

Tamoxifen enhances therapeutic effects of gemcitabine on cholangiocarcinoma tumorigenesis

Abstract: Cholangiocarcinoma is a highly malignant tumor with limited therapeutic options. We have previously reported that tamoxifen (TMX) induces apoptosis of cholangiocarcinoma cells and reduces cholangiocarcinoma tumorigenesis in mice.In the present studies, we determined the effect of combination therapy of TMX and gemcitabine (GMT), another chemotherapeutical reagent for many cancers, on cholangiocarcinoma tumorigenesis and investigated the responsible mechanisms. GMT inhibited cell growth and induced apoptosis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Besides patho-physiological studies [106113], this model is suitable for testing the efficacy of novel therapeutic approaches for CCA. Molecules like tannic acid, resveratrol, caffeic acid, anandamide, tamoxifen, felodipine, melatonin, and clobenpropit were shown to inhibit CCA xenograft tumour growth as did hematoporphyrin derivative-mediated photodynamic therapy, and oncolytic gene therapy,[114126]. Similarly, targeting CCA cells with Slug si-RNA increased tumour sensitivity to cisplatin [127].…”
Section: Experimental Models Of Ccamentioning
confidence: 99%
“…Besides patho-physiological studies [106113], this model is suitable for testing the efficacy of novel therapeutic approaches for CCA. Molecules like tannic acid, resveratrol, caffeic acid, anandamide, tamoxifen, felodipine, melatonin, and clobenpropit were shown to inhibit CCA xenograft tumour growth as did hematoporphyrin derivative-mediated photodynamic therapy, and oncolytic gene therapy,[114126]. Similarly, targeting CCA cells with Slug si-RNA increased tumour sensitivity to cisplatin [127].…”
Section: Experimental Models Of Ccamentioning
confidence: 99%
“…We and others have found that activating intrinsic apoptotic signaling pathways using gemcitabine (26), doxorubicin (27) or ionizing radiation (28), sensitizes resistant cancer cells to death receptors-induced apoptosis. These intrinsic apoptotic activators function via inducing mitochondria leakage or DNA damage (26-28). …”
Section: Introductionmentioning
confidence: 99%
“…Tamoxifen treatment induces apoptosis of breast cancer cells (19), cholangiocarcinoma cells (20) and rhabdomyosarcoma cells (21) at least in part through induction of caspase-3 activity. The stimulation of apoptosis by tamoxifen has been described in a number of tissues and pathological conditions.…”
Section: Discussionmentioning
confidence: 99%